(untitled) (Olhares, 2015)
The Field of Vision is a system of improvisation, which tries to stablish by means of action a communion between the concepts techné and psiché, procedures and method, body and soul. Based on the investigation along with the students from the Célia Helena School-Theater and with actors from Cia. Elevador de Teatro Panorâmico, the text presents an analytical approach about the system that is developed since 2000.